El catalanisme i el problema social : . Assambleas catalanistas : VII : Barcelona : deliberacions y acorts (Eumo [etc.], 1993)
Facs. de : Assambleas catalanistas : VII : Barcelona : deliberacions y acorts. - Barcelona : La Renaixensa, 1904.